Was the Spanish labor market reform of 2012 successful? : - Bondarevska, Anna (2016)
This thesis explores the efficiency of the reforms on the labor market of Spain in 2012. The main goal of this work is to evaluate the effectiveness of undertaken reform against its own objectives. Relevance of this topic is that after the Global Financial Crisis of 2008 many country s economic situation significantly worsened. Searching for the way out of the complicated and undesirable economic situation countries applied new reforms and development plans majority of which didnt contribute into the improvement of country s economy. Concerning this fact it appears extremely important to analyze measures undertaken by Spanish government and its efficiency. To evaluate the effect caused by the reforms I have analyzed long-term results of it its influence on the selected indicators and overall unemployment.